Analysis of Credential Methods with the Value of Ongoing Practice Professionalism Evaluation in A Private Hospital in Surakarta - Sujiyanti, Sujiyanti; Suyamto, Suyamto (GLOBAL HEALTH SCIENCE GROUP, 2024)
Nurses as professionals have a very important clinical role in realizing quality services oriented towards patient safety. To improve their performance, nurses are required to continuously improve their professionalism. Nurse performance is assessed using the Ongoing Professional Practice Evaluation (OPPE) assessment. Credentials are an effort to maintain the professionalism of nurses, but their implementation still varies. The credential method is carried out through several methods, namely viewing portfolios, interviews, written exams and practical exams. This study aims to determine differences in OPPE scores for nurses in the three groups of credentialing methods used. This research is a comparative descriptive study that compares OPPE in three groups of respondents who used the credential method, namely the group that used portfolios and interviews, portfolios, interviews and written tests; as well as portfolios, interviews, written exams and practical exams. The results of research on 60 respondents showed that the majority were aged 26 – 30 years (56.06%), female (66.7%), had a D3 education in Nursing (71.1%). The majority of OPPE scores are Good (66.67%) and the longer the nurse works, the better the performance score. There are differences in OPPE values for respondents who were credentialed using method 1, method 2 and method 3. The more credential methods used, the better the OPPE value obtained.